APPLICATION OF BEHAVIORAL COUNSELING WITH SELF-MANAGEMENT TECHNIQUES TO REDUCE DEVIANT BEHAVIOR STUDENTS OF SMA DWIJENDRA DENPASAR - Putu Agus Semara Putra Giri; Luh Ade Pradnyanica (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2023)
The goal to be achieved in this research is to reduce the deviant behavior of class X.1 students of SMA Dwijendra Denpasar, the academic year 2022/2023 through the application of behavioral counseling with self-management techniques. The research subjects were students of class X.1 who had highly deviant behavior totaling five students consisting of five male students. Based on the data and discussion of the research results, it can be concluded that (1) there is a decrease in deviant behavior individually and in groups. (2) the score of deviant behavior before the action as a group was 595 and an average of 119; after being given the action in cycle I became 484 and an average of 96.8 with a percentage decrease as a group of 92% with an average of 18.4%. In cycle II, the score decreased again to 310 and an average of 62 with a group percentage of 176% with an average of 35.2%. Thus the results of this study can be concluded that applying behavioral counseling with self-management techniques can reduce deviant behavior in class X.1 SMA Dwijendra Denpasar, the academic year 2022/2023.